Assessing of executive functions in daily life in preterm children aged 3–4 years old from the “Behavior Rating Inventory of Executive Function—Preschool version” questionnaire - Reynold de Seresin, Magali; Roy, Arnaud; Theveniaut, Camille; Le Goff, Justine; Chopin, Coline; Rouger, Valérie; Roze, Jean-Christophe; Flamant, Cyril; Muller, Jean-Baptiste (Frontiers in Pediatrics, 2023)
Background: Executive functions (EF) are a set of neuropsychological skills permitting solve problems in a new situation by regulating action, behavior, and emotional response. As cerebral maturation remains vulnerable in preterm children, a higher risk to develop cognitive disorders including EF exist comparatively to term children. Aims: The aim of this study was to estimate the incidence of preschool EF impairments through proxy-reports in children born preterm before 34 weeks of gestational age, using the Behavior Rating Inventory of Executive Function – Preschool version (BRIEF-P). Secondary aims were to report neonatal, child or socioeconomic factors associated with EF disorders. Results: Parents of 357 three- to four-year-old children born preterm completed the BRIEF-P. Impairment in EF was clinically significant for 13.5 % preterm children (n=47; 95% CI = 0.10-0.18) compared to 5.1 % in term children. A low parent socioeconomic level was significantly associated with impaired parent-rated EF (19.1% vs 5.3%, p = 0.003). Conclusions: Proxy-report of EF impairment is about twice as frequent as term children. EF difficulties are not related to neonatal or child severity factors by contrast with parent socioeconomic level. Using parent-rated questionnaire may be a useful and easy tool to early identify in daily life impact of EF disorders in clinical follow-up in preterm children. Study was recorded to Clinical Trials Register, by NCT03700463.